Amorphous FeNi-bimetallic infinite coordination polymers as advanced electrocatalysts for the oxygen evolution reaction. Issue 83 (2nd October 2019) - Ma, Junchao; Bai, Xiaojue; He, Wenxiu; Wang, Sha; Li, Linlin; Chen, Huan; Wang, Tieqiang; Zhang, Xuemin; Li, Yunong; Zhang, Liying; Chen, Junyi; Meng, Fanbao; et al.
Abstract : The synthesis of the FeNi-bimetallic ICP/NF is simple and fast, and the amorphous nanosheet-based material exhibits excellent performance during OER electrocatalysis. Abstract : Amorphous bimetallic coordination polymers have been prepared by a mild room temperature solution phase method and utilized as an OER electrocatalyst. Their excellent performance with an overpotential of 228 mV at 10 mA cm −2 and a Tafel slope of 30.3 mV dec −1 exhibits their great potential in the field of the OER.